Study on the Sealing Structure of Scroll Tooth of an Oil-free Scroll Compressor - Wang Jianji; Liu Tao (Zhileng xuebao)
A novel type of radial combined sealing structure was proposed to improve the end-face sealing of wraps between fixed and orbiting scrolls. Geometry and engineering fluid mechanics were considered to develop an algorithm for determining leakage from the tooth top of the base circular involute oil-free scroll compressor with a smooth clearance tip seal, labyrinth tip seal, and combination tip seal. A simulation platform to test adjacent compression chambers for scroll compressors was established to measure the gas leakage of three sealing structures under the same pressure difference. The experimental and theoretical calculation results were compared, and the theoretical calculations were identical to the measured results. The amount of leakage from the smooth seal and labyrinth seal increased as pressure difference increased, while the leakage amount of the combined seal was inversely proportional to the pressure difference. However, the wear amount of the seal increased. The measured leakage of the labyrinth seal was 80% that of the smooth seal, and the measured leakage of the combined seal was 63% that of the smooth seal. Thus, we can confidently conclude that the combination sealing structure is more suitable for large compression ratio scroll compressor applications. Furthermore, the radial leakage of these three sealing structures decreases as the speed of the moving scroll increases. This tends to be stable when the rotational speed exceeds 4000 m/s.